RECONSTRUCTION POLICY AGAINST DEVELOPMENT AUTHORITY TASKS AND INHERITANCE CERTIFICATE SUBMITTED TO THE COURT BASED ON SOCIAL JUSTICE VALUE - Nany Pudjianti Suwigjo; Gunarto Gunarto; Maryanto Maryanto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2019)
As is well known, at the moment there are three (3) form and three (3) agencies that can make the evidence as heir adjusted or ethnic groups resident or citizen of Indonesia. Classification of the population based on ethnicity and law that applies to every segment of the population is a legacy of the Dutch colonial government in Indonesia, which until now is considered a sacred rule that can not be changed by anyone, even by the state. Whereas in the framework of legal reform and build a socially just nation that such an arrangement should be reconstructed, because it is no longer compatible with our own independent nation. Classification of Indonesia's population contained in the rules on the manufacture evidence can be seen as heir historical factors of the Indonesian nation. Dutch East Indies government then run political divide et impera or divisive politics. Divide et impera is done by dividing the population of the archipelago within 3 (three) segments of the population, namely: Group Europe, Group Foreign Easterners (such as Chinese, Indian, Arab, Pakistani), and Group of the Indigenous, as stipulated in Article 163 Indische Staatsregeling (hereinafter called IS). The separation of the population with the population of groups based on ethnicity or race under Article 163 IS This resulted in a difference between the legal system applicable to each of these groups. Three population groups are subject to civil law that is different as stipulated in Article 131 and Article 75 RR IS. The distinction in this class brought with it differences in the civil law of each of these groups.Keywords:Authority; Certificate of Inheritance; Court; Social Justice.